PHACE syndrome in antenatally diagnosed posterior fossa anomaly - Seema Pavaman Sindgikar; Uppoor Raghuraj; Kishan Alva; Thomas Mathen Maveli (Wolters Kluwer Medknow Publications, 2014)
PHACE is a neurocutaneous syndrome, an acronym to describe patients with facial segmental hemangiomas and other malformations. We describe a newborn antenatally diagnosed to have posterior fossa anomaly and subsequently as PHACE syndrome.